Hornera currieae n. sp. (Cyclostomatida: Horneridae): a new bathyal cyclostome bryozoan with reproductively induced skeletal plasticity - Batson, Peter B.; Tamberg, Yuta; Gordon, Dennis P.; Negrini, Marianne; Smith, Abigail M. (Zootaxa, 2021)
Here we describe a new hornerid, Hornera currieae n. sp. (Bryozoa: Cyclostomatida) from bathyal depths across the New Zealand region. Colonies are irregular, finely branched fans attaining 40 mm or more in height. Key characters include: (1) thick, semi-hyaline porcellanous skeleton; (2) loss or reduction of nervi (longitudinal striae) away from growing tips; (3) sparse, threadlike cancelli; and (4) small (61–87 µm), widely spaced autozooidal apertures. Diagnostic hornerid traits possessed by H. currieae n. sp. include vertical ancestrular tube, periancestrular budding of daughter zooids, and skeletal ultrastructure dominated by hexagonal semi-nacre grading to pseudofoliated fabric. The abfrontal incubation chamber develops from a cryptic tube arising from the frontally positioned aperture of the fertile zooid. We used SEM, micro-CT and electron backscatter diffractometry (EBSD) to investigate the ultrastructure and internal architecture of H. currieae n. sp. EBSD reveals that crystalline c-axes of laminated crystallites are perpendicular to skeletal walls. Threadlike cancelli, which traverse secondary calcification, connect autozooidal chambers to the colony-wide hypostegal cavity. Micro-CT reveals that abfrontal cancelli usually bend proximally towards the base, but turn distally towards reproductively active regions of the colony in synchrony with gonozooid development. The zone of affected cancelli extends for 4–7 branch internodes below the gonozooid. We assessed whether skeletal ultrastructure was similarly affected, but neither cancellus direction, nor gonozooid proximity, were predictive of the crystallite imbrication direction. We hypothesise that (1) hornerid cancelli are active conduits for colonial metabolite transport and (2) that changes in gradients of metabolites and/or reproductive morphogens within the hypostegal cavity affect cancellus morphogenesis. Potentially, H. currieae n. sp. skeletons may preserve a record of intra-colony metabolite translocation dynamics over time.